Preservation of West Java Culinary Recipe Using Augmented Reality, Photogrammetry, and Storytelling Illustration - Remandhia Mulcki; Fransiska Rachel; Hermanto Laksana (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
Many traditional culinary recipes from West Java are lost because they are not well-documented; this is a concern for many parties. Losing the recipe means losing the "artifacts" of traditional culinary and precious history and philosophy, which are part of local wisdom. Therefore, modern documentation is needed, which is informative, interactive, engaging, and loved by the young generation. This research is about designing West Java traditional culinary recipes using augmented reality, photogrammetry, and storytelling illustration. This study employs action research. For the data collection method, structured interviews with West Java culinary lecturers and Assemblr Augmented Reality (AR) apps creators were used. Then, this data will be used as content for proposing a design solution. Based on the research conducted, the attempt to preserve West Java culinary recipes using augmented reality, photogrammetry, and storytelling illustration is determined by the extent of the fresh, fun, and fascinating concept in all these media to create an excellent first impression as an exciting medium. Once the audience is interested, the transfer of knowledge afterward will be smoother. Fun and funny illustrations can generate the desire to find and taste these traditional foods.